The role of schemes in the protection of real estate cultural property in Algerian legislation - FERDI, Karima (Journal of Human Sciences, 2025)
Real cultural properties serve as evidence to the Algerian state in particular, and to the Arab and Islamic nations in general. To prevent the disappearance of these landmarks, the Algerian legislator has given them particular attention by establishing legal mechanisms and preventive measures through various legal texts to provide effective protection for these properties. Additionally, there are specific legal mechanisms for protection detailed in particular regulations, including the protective role played by both central and local urban planning schemes, as well as special planning schemes dedicated to the preservation of cultural real estate. In this context, we raise a legal issue: Have these planning schemes, across successive laws, played an adequate role in extending legal protection to cultural real estate properties in Algeria? And if not, how can its protective role be activated?